Flambage plastique des coques cylindriques raidies axialement - Chapuliot, Stephane; Combescure, Alain (European Journal of Computational Mechanics, 1993)
A new analysis for plastic stability of axially stiffened shells is presented. It includes incremental analysis of plasticity and the evaluation of the appropriate tangent stiffness. In this approach a stiffened shell is considered as a multi-layer shell with one isotropic layer for the shell and one orthotropic layer for the stiffeners. Then in each layer an Ilyushin type of yield criterion, that is a direct function of the six stress resultants N, { M} and an equivalent plastic strain, is treated as a plastic potential. Flow rule is applied for plasticity and three various stress-strain matrix are given for the plastic stability analysis based on the flow theory. the tangent modu/ous theory and the deformation theory. A numerical study and an experiment on the plastic buckling of axially stiffened shell are compared.